Macroeconomic Impact on Non-Performing Financing in Islamic Banking in 2011-2021 - Hidayah, Aldila Nuri; Meylianingrum, Kurniawati (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2023)
This study aims to determine the effect of Gross Domestic Product (GDP), unemployment rate, inflation and debt on non-performing financing in the Middle East, Central Asia, and Indonesia for the 2011-2021 period. This research uses descriptive quantitative research methods. The data used in this study are secondary data with documentation data collection techniques and literature studies sourced from www.imf.org and financial statements. The data analysis technique used is multiple linear regression with Eviews 12 software. The results of this study show that GDP, unemployment rate, and inflation partially have not significant of non-performing financing. Meanwhile, debt has a positive and significant of non-performing financing.